Ideational and institutional drivers of social protection in Tanzania - Marianne S. Ulriksen (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
In the early 2000s, there was low elite commitment to social protection in Tanzania. Yet, in 2012, the government officially launched a countrywide social safety net programme, and a year later it announced the introduction of an old age pension. In this article, I explore the reasons for this recent elite commitment to social protection. The analysis takes an ideational approach, and it is shown how the promotion of social protection has been driven by international and domestic institutions with the resources, expertise, and authority to present policy solutions fitting the elite's general ideas about Tanzania's development challenges and possible responses thereto. Thus, ideas play an important role in policy development. Attention to the ideas of ruling elites also reveals cases where ideas lose prominence as an explanatory factor. The introduction of the pension fits poorly with dominant views on development and poverty reduction in Tanzania and is more likely to have been influenced by political interests.
Keywords: H55; I38; O55; P48; 330; social protection; ideas; institutions; policy entrepreneurs; political settlements; Tanzania